Актуалізація процедури формування фінансових ресурсів підприємства в умовах цифрової кономіки - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Строцький, В.В.; Strozkii, Vadym (Причорноморський науково-дослідний інститут економіки та інновацій, 2023)
У статті розкриваються основні принципи управління фінансовими ресурсами підприємств в умовах функціонування цифрової економіки України і світу. Авторами висвітлено основні складові механізму управління фінансовими ресурсами підприємств. Проведено огляд найбільш відомих підходів до визначення характеристик фінансових ресурсів підприємства, який показав багатомірність і різноплановість теоретичних і практичних поглядів на цю економічну категорію. Запропоновано узагальнений вигляд економічної категорії «фінансові ресурси» підприємств, який відображає його основні характеристики як елементу фінансового менеджменту підприємства. Розглянуто принципи ефективного управління фінансовими ресурсами підприємства, що забезпечується реалізацією поставлених перед ним завдань і мети. Визначено основоположні аспекти системи управління фінансовими ресурсами підприємства як складової фінансового менеджменту. The article reveals the main principles of managing the financial resources of enterprises in the conditions of functioning of the digital economy of Ukraine and the world. The authors highlighted the main components of the mechanism for managing the financial resources of enterprises. An overview of the most well-known approaches to determining the characteristics of the financial resources of the enterprise was conducted, which showed the multidimensionality and diversity of theoretical and practical views on this economic category. A generalized view of the economic category «financial resources» of enterprises is proposed, which reflects its main characteristics. A generalized view of the economic category "financial resources" of enterprises is proposed, which reflects its main characteristics as an element of the financial management of the enterprise. The principles of effective management of the company's financial resources, which is ensured by the implementation of the tasks and goals set before it, are considered. The fundamental aspects of the system of managing the company's financial resources as a component of financial management are determined. It is proved that the formation of the financial resources of the enterprise is one of the most significant functional areas of the financial management system. It is closely related to other enterprise management systems. Management of financial resources is organically included in the system of income and expenditure management, management of the movement of assets and capital, management of all aspects of operational, investment and financial activities of the enterprise. When managing the formation of financial resources, it is necessary to determine the optimal structure and volume of funds, which affects the constant solvency of enterprises, as well as creates prerequisites for the further prospective development of the enterprise. The procedure for forming the company's financial resources must take into account the system of factors of the economic environment in which the company carries out its production and economic activities.
Update of the procedure for the formation of financial resources of the enterprise in the conditions of the digital economy
Keywords: фінансові ресурси; financial resources; фінансування; financing; грошові кошти; cash; грошові потоки; cash flows; цифрова економіка; digital economy